Comprehensive definition of genome features in Spirodela polyrhiza by high‐depth physical mapping and short‐read DNA sequencing strategies. (3rd February 2017) - Michael, Todd P.; Bryant, Douglas; Gutierrez, Ryan; Borisjuk, Nikolai; Chu, Philomena; Zhang, Hanzhong; Xia, Jing; Zhou, Junfei; Peng, Hai; El Baidouri, Moaine; ten Hallers, Boudewijn; Hastie, Alex R.; et al.
Summary: Spirodela polyrhiza is a fast‐growing aquatic monocot with highly reduced morphology, genome size and number of protein‐coding genes. Considering these biological features of Spirodela and its basal position in the monocot lineage, understanding its genome architecture could shed light on plant adaptation and genome evolution. Like many draft genomes, however, the 158‐Mb Spirodela genome sequence has not been resolved to chromosomes, and important genome characteristics have not been defined. Here we deployed rapid genome‐wide physical maps combined with high‐coverage short‐read sequencing to resolve the 20 chromosomes of Spirodela and to empirically delineate its genome features. Our data revealed a dramatic reduction in the number of the rDNA repeat units in Spirodela to fewer than 100, which is even fewer than that reported for yeast. Consistent with its unique phylogenetic position, small RNA sequencing revealed 29 Spirodela‐specific microRNA, with only two being shared with Elaeis guineensis (oil palm) and Musa balbisiana (banana). Combining DNA methylation data and small RNA sequencing enabled the accurate prediction of 20.5% long terminal repeats (LTRs) that doubled the previous estimate, and revealed a high Solo:Intact LTR ratio of 8.2. Interestingly, we found that Spirodela has the lowest global DNA methylation levels (9%) of any plant species tested. Taken together our results reveal a genome that has undergone reduction, likely through eliminating non‐essential protein coding genes, rDNA and LTRs. In addition to delineating the genome features of this unique plant, the methodologies described and large‐scale genome resources from this work will enable future evolutionary and functional studies of this basal monocot family. Significance statement: Spirodela polyrhiza is a fast‐growing aquatic and basal monocot with a small genome, so understanding its genome architecture should inform plant adaptation strategies and genome evolution. However, long repetitive regions are formidable challenges for the proper assembly, annotation and closure of genome projects. Here we overcame this bottleneck by combining high‐throughput sequencing and genome mapping technologies to generate a validated sequence map of the 20 Spirodela polyrhiza chromosomes. Genome‐wide profiling data revealed a genome in a cycle of reduction with very low global DNA methylation and a reduced ribosomal DNA as well as gene content.